LDHA Promotes Oral Squamous Cell Carcinoma Progression Through Facilitating Glycolysis and Epithelial–Mesenchymal Transition - Cai, Hongshi; Li, Jiaxin; Zhang, Yadong; Liao, Yan; Zhu, Yue; Wang, Cheng; Hou, Jinsong (Frontiers in Oncology, 2019)
Aerobic glycolysis is the main pathway for energy metabolism in cancer cells. It provides energy and biosynthetic substances for tumor progression and metastasis by increasing lactate production. Lactate dehydrogenase A (LDHA) promotes glycolysis process by catalyzing the conversion of pyruvate to lactate. Despite LDHA exhibiting carcinogenesis in various cancers, its role in oral squamous cell carcinoma (OSCC) remains unclear. This study demonstrated that LDHA was over-expressed in both OSCC tissues and cell lines, and was significantly associated with lower overall survival rates in patients with OSCC. Using weighted gene correlation network analysis and and gene set enrichment analysis for the gene expression data of patients with OSCC (obtained from The Cancer Genome Atlas database), a close association was identified between epithelial–mesenchymal transition (EMT) and LDHA in promoting OSCC progression. The knockdown of LDHA suppressed EMT, cell proliferation, and migration and invasion of OSCC cells in vitro. Moreover, the silencing of LDHA inhibited tumor growth in vivo. Oxamate, as a competitive LDHA inhibitor, was also suppressed diverse malignant biocharacteristics of OSCC cells. Our findings reveal that LDHA acts as an oncogene to promote malignant progression of OSCC by facilitating glycolysis and EMT, and LDHA may be a potential anticancer therapeutic target.